GAME SIMULASI BELAJAR PEMBAGIAN BERBASIS MULTIMEDIA UNTUK ANAK KELAS 5 - Sudaryana, I Ketut; Doharma, Rouly (ISTEK WIDURI, 2019)
Learning to count for school children becomes a daunting subject matter, difficult because it requires thinking and using reasoning to solve it. As material that has been taught since elementary school, media are needed that can help students learn to count. To overcome students' difficulties in learning to count, Diginusa has special counting software for grade 5 children, based on multimedia that combines elements of text, sound, images and animation. The purpose of this study is to make learning to count easier because it is done in the form of a visualization on a computer monitor screen. This research utilizes quantitative data types, with data collection obtained from the results of software experiments to students in the form of grades that will be compared with the KKM scores. The Tecknology Acceptance Model (TAM) application is used to measure acceptance of interactive learning media. This TAM model illustrates the acceptance of the use of information technology that is strongly influenced by usefulness. The results of this study are from two data that are processed based on Minimum Completeness Criteria (KKM) whose percentage is 97% and the results of the Questionnaire are 64%.